Solve it -√cosx-1/coax+1
Answers
Answered by
0
heya friends ☺
√cox-1/cosx+1
√cosx-1/cosx+1×√cosx+1/cosx+1
multiply by √cosx+1 on nemunator and denominator
then..we get..
(√cos²x-1²/(√cosx+1)²
=> -(1-cos²x)/cosx+1
=>-√sin²x/cosx+1
=>-sinx/cosx+1
=>-tanx-sinx
-(tanx+sinx) Ans .
hope it helps you.
.
@Rajukumar
√cox-1/cosx+1
√cosx-1/cosx+1×√cosx+1/cosx+1
multiply by √cosx+1 on nemunator and denominator
then..we get..
(√cos²x-1²/(√cosx+1)²
=> -(1-cos²x)/cosx+1
=>-√sin²x/cosx+1
=>-sinx/cosx+1
=>-tanx-sinx
-(tanx+sinx) Ans .
hope it helps you.
.
@Rajukumar
Similar questions